Comparação entre termos de indexação e palavras dos títulos dos artigos do periódico "Cadernos de Saúde Pública (2000/2005)" - Elizabeth Andrade Duarte (2007)
The present research intends to verify if the indexing terms given to published articles in Scientific Journal of Public Health would be in the titles of those articles. It wants to analyze the indexing process from articles of that Journal, as well as, compares the indexation made by indexers / authors with a possible automatic indexation, considering the terms, which were found in the titles of those articles. The presumptions of this research are: the titles can identify the content of a scientific paper; the indexing process of scientific articles influences on the restoring of the information; the titles of the articles not ever represent the restore of the information and the proposed key-words, however, can go beyond the titles and allow a semantic detailing (specific content, details), coming from a large range of different points of view, which, sometimes, can also be influenced by the subjectivity in the indexing process. The following subjects consist on the theoretical basis and were found in the national and international literatures: scientific production, documentary language, scientific communication, scientific journals spreading of scientific information, analysis, restoring, bibliometry and bibliometric indexes. Discussion, analysis and evaluation of the results of scientific activity in a pre established period was the selected methodology through the National Data Base and all the 895 articles from the scientific journal Cadernos de Saúde Pública, published from 2000 to 2005. Data were developed by a survey of indexing subjects (on average 3707 terms), and analysis has used statistic methods and interpretation. The analyzes tried to find the percentage of indexing subjects, as well as the relevance of bibliometric indexes in the spreading of the built and investigated knowledge, and overall, to check the quality of restoring from an electronic data-base. Results have shown a great number of different terms when compare the key-words used in indexation and the words found in the titles of the articles. This research could improve the dynamic of the daily work of professionals from Information Science and correlated ones.